Autobiographic Resonances in the Orks of Fadwa Tuqan - Alkhouli, Khitam (Dirasat: Human and Social Sciences, 2022)
This study explores autobiographic resonances in the works of Palestinian writer and poet Fadwa Tuqan who wrote her biography in two parts: A Mountainous Journey, 1985, and the Most Difficult Journey 1993. Focusing on a range of devices that combine narrative, dialogue, and straightforward documentation, her autobiographic works merge the literary and the historic, the social and the political, with protest poetry featuring as a prominent form in her oeuvre. This study focuses on exploring the following themes: The Sisyphean aspect: Incorporating the semantics of futility of perseverance using the symbolism of the Greek myth Sisyphus entailed in her poetic works: A Mountainous Journey and the Most Difficult Journey. The Interior World: Focusing on familial oppression as well as colonialist practices and political oppression. Breaking Taboos: Subverting societal patriarchy and unleashing emotional expression are two prominent aspects of her poetry; representing her quest for liberation and ridding herself of the shackles of societal confinement in a male-chauvinistic society. By exploring these three components in Tuqan’s works, the study unveils the inner workings of the poet’s world as she quests to find intellectual enlightenment whilst confronting political and personal strife. The autobiography reflects not only her personal confinement as a female in a male-dominated society but also her confinement in an occupied nation. By combining a multitude of poetic devices, Fadwa Tuqan’s works evoke her deep and personal existential angst.